PENGARUH PERSEPSI KEMUDAHAN DAN CASHBACK TERHADAP PERILAKU KONSUMSI ISLAM PADA PENGGUNA SHOPEEPAY - Reni Widiyanti; Khusnul Fikriyah (ITB AAS Indonesia Surakarta, 2023)
This research aims to determine the effect of convenience perception and cashback on Islamic consumption behavior on shopeepay users, especially in the Z Generation of Mojokerto Regency. Islamic consumption behavior is measured by five basic principles of Islamic consumption behavior. The research method is associative quantitative. The sample in this research are 100 respondents of generation Z in Mojokerto Regency who are shopeepay users by using the Hair formula. Data collection uses a questionnaire distributed via google form by using a purposive sampling method and using a Likert scale. Data processing uses the help of SmartPLS version 4.0 software with the SEM-PLS analysis method. The results of the research show that perceived convenience and cashback have an influence on the consumption behavior of Z Generation in using Shopeepay.